Inisiasi Program Kidspreneur Pada LKSA Panti Asuhan Hasbi Rabbi Bandar Lampung - Marvinita, Risda; Fathia, Syaharani N; Nabila, Nuzul Inas; Banuwa, Laili F; Sari, Aida (STMIK Royal, 2024)
The Kidspreneur program was created with the aim of building the mental and mental independence of children from an early age, enhancing entrepreneurial motivation, improving their knowledge and skills of entrepreneurship, as well as teaching them how to promote business products, develop their knowledge and entrepreneur skills, and develop their company's product marketing skills. The service of this community was carried out at the LKSA Panti Asuhan Hasbi Rabbi Bandar Lampung on July 10–14, 2023. The method used is participatory, involving partners in various stages of activities such as training, the practice of entrepreneurial ideas, and support. The results of these activities are motivating and encouraging participants to become entrepreneurs at a young age, enhancing entrepreneurial skills and ideas, and getting information about digital marketing. Benefits of this activity in addition to the success of the government program in the realization of the program Kota Bandar Lampung Ramah Anak. It is also expected to be an additional source of income or even a primary source of search to reduce the dependence of orphanage members on donations in order to realize the financial independence of the orphans. Keywords: kidspreneur; training; orphanage Abstrak: Program Kidspreneur dibuat dengan tujuan untuk membangun mental dan jiwa kemandirian anak sejak usia dini, meningkatkan motivasi kewirausahaan, meningkatkan pengetahuan dan keterampilan kewirausahaan, serta mengajari mereka cara mempromosikan produk bisnis, pengetahuan dan kemampuan kewirausahaan, dan mengembangkan keterampilan pemasaran produk perusahaan mereka. Kegiatan pengabdian masyarakat ini dilaksanakan di LKSA Panti Asuhan Hasbi Rabbi Bandar Lampung pada tanggal 10-14 Juli 2024. Metode yang digunakan adalah bersifat partisipatif, dengan melibatkan mitra dalam berbagai tahapan kegiatan seperti pelatihan, praktik ide kewirausahaan, serta pendampingan. Hasil dari kegiatan ini adalah memotivasi dan mendorong peserta untuk menjadi wirausahawan di usia muda, meningkatkan keterampilan dan ide kewirausahaan, serta mendapatkan informasi mengenai pemasaran digital. Manfaat dari kegiatan ini bentuk kontribusi pada program pemerintah dalam mewujudkan program Kota Bandar Lampung Ramah Anak. Diharapkan juga dapat menjadi sumber penghasilan tambahan atau bahkan sumber pencarian utama untuk mengurangi ketergantungan anggota panti asuhan terhadap donatur demi mewujudkan kemandirian finansial anggota panti asuhan.Kata kunci: kidspreneur; pelatihan; panti asuhan